2020
DOI: 10.1097/pcc.0000000000002425
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Pediatric Critical Care Resource Utilization for Disaster Triage*

Abstract: Objectives: Pediatric protocols to guide allocation of limited resources during a disaster lack data to validate their use. The 2011 Pediatric Emergency Mass Critical Care Task Force recommended that expected duration of critical care be incorporated into resource allocation algorithms. We aimed to determine whether currently available pediatric illness severity scores can predict duration of critical care resource use. Design: Retrospective cohort study. Setting: Seattle Children's Hospital. Patients: PICU pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Additionally, our review is focused on an adult critical care setting as pediatric populations use different types of triage criteria. Resource allocation and triage in pediatric groups has been explored elsewhere [122,123]. Regardless of the operating characteristics, healthcare systems need to decide which triage protocol to enact if the demand of critical care resources exceeds supply to ensure a standardized and ethically sound approach to allocating health resources.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our review is focused on an adult critical care setting as pediatric populations use different types of triage criteria. Resource allocation and triage in pediatric groups has been explored elsewhere [122,123]. Regardless of the operating characteristics, healthcare systems need to decide which triage protocol to enact if the demand of critical care resources exceeds supply to ensure a standardized and ethically sound approach to allocating health resources.…”
Section: Discussionmentioning
confidence: 99%
“…We developed and validated such a tool using data derived from the Virtual PICU System database and demonstrated that its use would result in improved population survival compared with random allocation, employing a virtual pandemic modeled after the 1918-1919 Spanish influenza outbreak (6, 7); but the tool was novel and unfamiliar to the general population of pediatric intensivists. Hence, the publication by Killien et al (8) in this issue of Pediatric Critical Care Medicine using a variation of the 12-hour Pediatric Logistic Organ Dysfunction (PELOD)-2 score ( 9) is a welcome addition to these efforts. That score, when added to selected additional, readily accessible variables, strongly predicted use and duration of PICU resources, particularly mechanical ventilators, with an area under the receiver operating characteristic curve greater than 0.900.…”
mentioning
confidence: 99%
“…Indeed, when only children not intubated at the time of the score's calculation were considered, the discriminatory power of the score was much reduced. Additional considerations, including the score's derivation from data from a single center, and the exclusion of children with primary cardiac diagnoses and neonates, further limit the generalizable predictive strength of the proposed score, as noted by the authors (8).…”
mentioning
confidence: 99%
See 2 more Smart Citations